AN ETHNOSEMANTIC STUDY ON PESANTREN LEXICON AS AN EFFORT FOR CULTIVATING CHARACTER EDUCATION - Elisa Nurul Laili; Sakhi Herwiana (MABASAN, 2019)
Formal, informal and non-formal educations are major milestones of post-family care that concern with shaping the character of their students. One form of education which has always been the choice of the majority of parents is pesantren education. Tradition in pesantren is a miniature of community tradition that deserves to be called a community which certainly has a major influence on the mindset and behavior of the students and alumni. One of traditions is the usage of a typical pesantren lexicon. The pesantren lexicon is one of the indirect efforts in character-building education. As it is well known, the majority of students in pesantren have good character as one of the goal of education carried out in pesantren. The educational process in the context of a pedagogical social environment such as pesantren is very interesting to be studied further so that it can be carried out also in the scope of other formal, informal, and non-formal education. This research is conducted to study the pesantren lexicons as an effort to plant character education in pesantren. This research usees ethnolinguistics theory by applying descriptive qualitative design.